Persepsi Dan Hambatan Tenaga Medis Dalam Penerapan Clinical Pathway: Literatur Review - Muhammad, Hana Yulianti; Saleh, Ariyanti; Rachmawaty, Rini (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Clinical pathways involve the health team and part of the patient's records. Hence, team dynamics become a principal factor that needs to be appraised during implementation. Clinical pathways were considered as an additional workload for medical personnel. This research aims to review articles that discuss the perceptions and barriers among medical personnel in implementing clinical pathways. The articles were searched through the PubMed, Willey, ProQuest, and Google Scholar databases, which were published no less than ten years period from 2010 to 2020. The keywords used perception OR response AND barriers OR obstacles AND clinical pathway OR care. The pathway corresponds to the title and purpose of the review and is in full-text form. In total, eight articles meet the review criteria and objectives. The results showed that clinical pathways are perceived as a process that is directed at realizing benefits, creating habits, and requiring enthusiasm, support, and time. Obstacles for medical personnel that often arise in implementing clinical pathways include not having enough time, lack of direction and guidance, lack of staff awareness, lack of compliance in documentation, and lack of staff commitment. Conducting a direct study on evaluating the implementation of clinical pathways in hospitals is recommended.